The Step-Down Challenge Service user perspectives on the realities of moving-on in residential care - Daly, Antony; Arnavut, Fatma; Bohorun, Dhiren (International Journal of Psychosocial Rehabilitation, 2018)
A series of interviews was carried out by a Counselling Psychologist and Assistant Clinical Psychologist based in a community mental health team in South East London to discover what its Service Users believe helps them to step down through levels of supported accommodation. The aim was to increase understanding of Service User perspectives of ‘step-down care’ and give insight into ways to facilitate movement out of high-support residential care settings. A qualitative thematic analysis was used to analyse the data following a series of semi-structured interviews with Service Users. The results showed that there was ambivalence among Service Users around step-down care and that there was more that residential care homes could be doing to prepare Service Users for stepping down.